Extended Reality Solutions in Medical Context and Educational Approaches...21st International Conference on Informatics, Management, and Technology in Healthcare (ICIMTH), July 1-3, 2023, Athens, Greece. - JANK, Miran; WAGNER, Fabian; URBAUER, Philipp; BALZ, Andrea; FORJAN, Mathias (Studies in Health Technology & Informatics, 2023)
The healthcare sector is growing in importance as people continue to age and pandemics complicate the boundary conditions of such systems. The number of innovative approaches to solve singular tasks and problems in this area is only slowly increasing. This is particularly evident when looking at medical technology planning, medical training and process simulation. In this paper a concept for versatile digital improvements to these problems by using state of the art development methods of Virtual Reality (VR) and Augmented Reality (AR) are presented. The programming and design of the software is done with the help of Unity Engine, which provides an open interface for docking with the developed framework for future work. The solutions were tested under domain specific environments and have shown good results and positive feedback.